Analysis of the correlation between operational performance and profitability over time in public hospitals - Ahmad, Syed Raziuddin; Khan, Imran Ahmad (Nurture, 2024)
Purpose The public hospitals are not-for-profit entities, and their purpose is not to generate and distribute profits as a result of business activities. Therefore, in the context of hospital management, where many hospitals are running into losses and improving profitability has become a major issue, it is necessary to study the relationship between operational performance and profitability. Design/Methodology/Approach: In this study, targeting public hospitals, an empirical study was attempted on the correlation between operational performance and profitability. The 303 hospitals were analyzed for the financial years 2022 and 2023. To confirm the validity of the results for the entire group of public hospitals (population), including hospitals other than those subject to this analysis, an uncorrelated test was conducted. Findings: As a result, there was a positive correlation between the volume of surgeries performed and profitability. On the other hand, the shortening of the average length of hospital stay did not lead to an improvement in profitability. Profitability improved as the number of inpatients per physician increased, but there was no correlation between the number of outpatients per physician and profitability. Conclusion: The results of this study suggest the importance of index correction.